THE ROLE OF ACCOUNTING AND INTERNAL CONTROL SYSTEMS IN ENSURING THE QUALITY OF FINANCIAL REPORTING IN HIGHER EDUCATIONAL INSTITUTIONS - Ermatova Sakhodatkhon , Ismailovna (THE INNOVATION ECONOMY, 2025)
This article examines the role of liabilities accounting and internal control systems in ensuring the quality of f inancial reporting in Uzbekistan’s higher education institutions (HEIs). The study investigates the impact of liabilities accounting on the accuracy and transparency of reports and the significance of internal control systems in optimizing financial processes. A mixed-methods approach was employed, combining qualitative analysis (of regulatory documents and HEI records) and quantitative analysis (of financial metrics from 5 HEIs over 2020–2024). Findings indicate that accurate liabilities accounting and effective internal control systems enhance reporting quality, yet challenges such as insufficient staff qualifications, infrastructure limitations, and regulatory inconsistencies persist. The article provides practical recommendations for improving financial management in HEIs.